2015
DOI: 10.1002/chem.201500533
|View full text |Cite
|
Sign up to set email alerts
|

Guapsidial A and Guadials B and C: Three New Meroterpenoids with Unusual Skeletons from the Leaves of Psidium guajava

Abstract: A novel sesquiterpene-based Psidium meroterpenoid, possessing an unusual coupling pattern, and two new monoterpene-based meroterpenoids with unprecedented skeletons were isolated from the leaves of Psidium guajava. Their structures and absolute configurations were elucidated by spectroscopic, X-ray diffraction, and computational methods. The plausible biosynthetic pathway of these meroterpenoids as well as their cytotoxicities toward HepG2 and HepG2/ADM cells were also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The 1 H and 13 C NMR data of 4 bore a high resemblance to those of guapsidial A ( 17 ) 11 , with the major differences occurring at C-3′, C-7′, and C-8′ of the benzoyl-phloroglucinol moiety (Δ δ C  = 2.3, 1.9, and 1.6 ppm, respectively), indicating that 4 possessed a different substitution pattern at the phloroglucinol unit. The locations of 5′-OH, 7′-OH, and 15′-CHO were assigned by HMBC correlations from the corresponding protons to C-5′, C-7′, and C-6′, respectively (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The 1 H and 13 C NMR data of 4 bore a high resemblance to those of guapsidial A ( 17 ) 11 , with the major differences occurring at C-3′, C-7′, and C-8′ of the benzoyl-phloroglucinol moiety (Δ δ C  = 2.3, 1.9, and 1.6 ppm, respectively), indicating that 4 possessed a different substitution pattern at the phloroglucinol unit. The locations of 5′-OH, 7′-OH, and 15′-CHO were assigned by HMBC correlations from the corresponding protons to C-5′, C-7′, and C-6′, respectively (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Biosynthetically, they are proposed to be adducts of phloroglucinol derivatives and terpenoids via hetero-Diels-Alder or carbocation-induced stepwise reactions 6, 10 . So far more than 100 phloroglucinol-coupled terpenoids have been reported 11, 18 , and their intriguing structures and important biological activities have attracted broad interest from both natural products and synthetic chemists over the last half century 5, 1924 . For instance, psiguadials A, C, and D 9, 10 , hyperjapones A–E 16 , and hyperjaponols A and C 17 with novel skeletons and appealing pharmacological activities (e.g., antitumor and antiviral properties) have been synthesized by several groups 25, 26 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative stereochemistry of H-8′ could not be established by above NMR information due to the flexibility of C-7′-C-8′ bond. In order to establish the stereostructure of 1, a quantum chemical ECD calculation was performed [17]. The TDDFT calculated CD spectra of four potential stereo-isomers of 1 were compared with the experimental one, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, it is assumed that these meroterpenoids arise from the crucial phloroglucinol precursor leptospermone coupled with mono-or sesquiterpenoid precursors through various conjugation manners to form diverse carbon skeletons. As a part of our ongoing investigation on searching for structurally unique and biologically interesting constituents from plants of family Myrtaceae [16][17][18][19][20], a new meroterpenoid, tomentodione E (1), along with four known ones (2)(3)(4)(5) were isolated from the leaves of R. tomentosa (Figure 1). Tomentodione E (1) possesses a skeleton which arose from a sec-pentyl syncarpic acid incorporating with a caryophyllene moiety, and compound 2 was reported from the titled plant for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Its leaves have been used as a folk medicine for the treatment of diarrhea and diabetes in China14. Previous investigations of the plant collected from Vietnam and Subtropic China have revealed that this plant is an abundant source of meroterpenoids151617. Considering the fact that the plant secondary metabolites could be influenced significantly by the ecological environment, we examined the leaves of P. guajava collected from Panzhihua city of Sichuan province, China.…”
mentioning
confidence: 99%